Pasture production, diet selection and liveweight gains of cattle grazing Brachiaria brizantha with or without Arachis pintoi at two stocking rates in the Atlantic zone of Costa Rica - Hernández, M.; Argel M., Pedro J.; Ibrahim, MA; Mannetje, L (1995)
Pastures of Brachiaria brizantha (Bb) alone or with Arachis pintoi (Bb + Ap) were rotationally grazed by 3 (LSR) and 6 (HSR) hd/ha. Mean 4-weekly forage DM on offer ranged from 3.5 t/ha at the HSR for Bb to 6 t/ha at the LSR for both pasture types. Mean dry weight proportion of Ap was 6% at the LSR and 34% at the HSR. The amount of Ap in the diet of steers was about 50% at the HSR and 10% at the LSR. During two 7-day grazing cycles, the mean crude protein concentration of the diet at both stocking rates in Bb and at the LSR in Bb + Ap ranged from 7 9.5%, but at the HSR in Bb + Ap, it ranged from 15 18%. In vitro dry matter digestibility of the diet ranged from 61 66% in all treatments, except for Bb at the HSR in which it fell to 54.1 % on the last day of grazing. Average daily gain was lowest for Bb at the HSR (291 377 g) and highest for Bb + Ap at the LSR (452 551 g). The mean annual liveweight gain (LWG) per animal ranged from 119 kg for Bb at HSR to 178 kg for Bb + Ap at the LSR. LWGha/yr ranged from 478 kg for Bb at the LSR to 937 kg for Bb + Ap at the HSR. Including Ap increased LWG/ha by 30% at the HSR and 11 % at the LSR. It was concluded that Ap is the best herbaceous legume presently available for the humid tropics of Costa Rica.